Measurement of sST2 is comparable to PlGF in the diagnosis of early-onset pre-eclampsia - Southcombe, J; Benton, S; Hu, Y; Von Dadelszen, P; Child, T; Snider, J; Redman, C; Sargent, I; Granne, I (2013)
A diagnostic test to confirm pre-eclampsia would be beneficial for the clinical management of the syndrome. The Triage PlGF test is able to confirm pre-eclampsia with high accuracy, with the greatest efficacy at <35 weeks gestation. We recently found that the anti-inflammatory protein sST2 is elevated in the plasma of pre-eclamptic women compared to normal controls. Here sST2 and PlGF are compared in early-onset and late-onset pre-eclamptic women. sST2 was found to be an equally good diagnostic tool for early-onset (sST2 AUC 0.944 versus PlGF AUC 0.995; not significant) but not late-onset disease. © 2013 International Society for the Study of Hypertension in Pregnancy. Published by Elsevier B.V. All rights reserved.